Symposium - Promising Practices in Scholar-Union Collaboration: Lessons for Building Effective Research Partnerships - Armstrong, Pat; Bittman, Kevin; Hurley, Michael; Stanford, Jim; Tucker, Sean; Vela, Jakin; Weststar, Johanna; Wilson, Fred (Relations industrielles / Industrial Relations, 2025)
This symposium considers the prospects for research collaboration between industrial relations scholars and trade unions, as well as its challenges. First, in remarks presented in the 2025 H.D. Woods Lecture at the Canadian Industrial Relations Association / Association canadienne des relations industrielles conference, Jim Stanford reviews the mutual benefits for both scholars and trade unionists from successful research partnerships and proposes strategies for building more respectful and trusting relationships between them. The symposium then presents three case studies of lasting, productive research partnerships, each described by a matched pairing of a scholar with a union representative. Lessons are drawn for future research collaborations.

Control and Insecurity in Australian and Canadian Universities during the COVID-19 Pandemic - Peetz, David; O’Brady, Sean; Weststar, Johanna; Coles, Amanda; Baird, Marian; Cooper, Rae; Charlesworth, Sara; Pyman, Amanda; Ressia, Susan; Strachan, Glenda; Troup, Carolyn (Relations industrielles / Industrial Relations, 2022)
We studied 14 universities across Canada and Australia to examine how the COVID-19 crisis, mediated through management strategies and conflict over financial control in higher education, influenced workers’ job security and affective outcomes like stress and happiness. The countries differed in their institutional frameworks, their union density, their embeddedness in neoliberalism and their negotiation patterns. Management strategies also differed between universities. Employee outcomes were influenced by differences in union involvement. Labour cost reductions negotiated with unions could improve financial outcomes, but, even in a crisis, management might not be willing to forego absolute control over finance, and it was not the depth of the crisis that shaped management decisions.
Keywords: Analyse comparative; Australia; Australie; COVID-19; Canada; Contrôle; Covid-19; Stratégies de gestion; Syndicat; Travailleurs universitaires; comparative analysis; control; contrôle financier; financial control; management strategies; negotiation pattern; négociation collective; union; university workers